Comparative study of the negative bending behaviour of corrugated web steel–concrete composite beams using NC, ECC and UHPC. (15th May 2023) - Wu, Fangwen; Fan, Zhou; He, Lanqing; Liu, Shuo; Zuo, Jian; Yang, Fei
Highlights: Negative bending behaviour of corrugated web composite beams using different concrete was discussed. Parameter influence on negative bending performance of composite beams was explored. Prediction formula of negative bending capacity of corrugated web composite beams was derived. Abstract: Engineered cementitious composites (ECC) and ultra-high performance concrete (UHPC) could significantly enhance the cracking performance of the negative bending regions of composite beams. In this study, the negative bending behaviour of corrugated web composite beams using normal concrete (NC), ECC and UHPC was comparatively discussed. Firstly, the negative bending test was performed for three composite beams using different concrete. The results showed that the failure modes of the corrugated web composite beams were characterized by local buckling of the steel beam compressed flanges and severe cracking of the concrete slabs. The negative bending capacity of the composite beams using UHPC increased by 17.9% and 14.4% compared to those using NC and ECC, respectively. Besides, finite element simulation indicated that the negative bending performance of steel-ECC composite beam was particularly affected by steel strength and reinforcement strength, and that of steel-UHPC composite beam showed the most significant response to steel strength. Furthermore, the negative bending capacity formula in the code was found conservative in predicting corrugated web composite beams, especially for those using UHPC. With the consideration of the tensile strength of concrete and the omission of the contribution of corrugated webs, a reasonable formula for predicting the corrugated web composite beams using different concrete was proposed and proved to have satisfactory accuracy.